2018
DOI: 10.1080/25726641.2018.1521578
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting nickel upgrade during selective grinding of low-grade limonitic laterites

Abstract: In this study wet grinding batch experiments were performed in a laboratory ball mill using laterites from Evia island, Greece, in order to determine the optimal grinding conditions for potential nickel upgrade. Selective grinding which exploits the different grindability between soft and hard minerals was considered. Kinetic models were determined based on population balance considerations for different feed and ball sizes. The efficiency of selective grinding was evaluated by taking into account breakage kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…It is also revealed that the smallest balls (12.7 mm size) are suitable for efficient grinding of slag (K ranged from 0.0017 to 0.1333), whereas the use of larger balls (40 mm) results in a much smaller breakage rate (K ranged from 0.0008 to 0.0614). So far, various attempts have been made to define the optimum grinding media size and improve the efficiency of ball milling [30,[56][57][58][59][60][61]. It has been found that the optimum ball size depends on several factors, including the feed/product size ratio, the mill dimensions, and the breakage parameters.…”
Section: Grinding Kineticsmentioning
confidence: 99%
“…It is also revealed that the smallest balls (12.7 mm size) are suitable for efficient grinding of slag (K ranged from 0.0017 to 0.1333), whereas the use of larger balls (40 mm) results in a much smaller breakage rate (K ranged from 0.0008 to 0.0614). So far, various attempts have been made to define the optimum grinding media size and improve the efficiency of ball milling [30,[56][57][58][59][60][61]. It has been found that the optimum ball size depends on several factors, including the feed/product size ratio, the mill dimensions, and the breakage parameters.…”
Section: Grinding Kineticsmentioning
confidence: 99%
“…Hence, the results of the present study show that the usual industrial practice of using higher milling rate does not necessarily result in efficient separation between the different minerals of interest present in ores or concentrates. Thus, detailed grinding kinetics analysis is required in order to determine the optimum grinding conditions that maximize the breakage rate of the minerals of interest, as for example diaspore in this case, while minimizing the respective rate of the impurities [55]. Al2O3 grade increases marginally from 63.5 to 64 wt% with increasing fc from 5% to 10% and then drops to 62.6 wt% when fc was 15%.…”
Section: Al2o3 and Fe2o3 Content Of The Selective Grinding Productsmentioning
confidence: 99%
“…The ball mill is powered by a motor connected to a belt. The number of balls (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), the duration of the grinding (5-15 minutes), and the rotation speed of the ball mill were the experiment's independent variables (8-16 rpm). The mass and diameter of each steel ball used in this study are shown in Table 2.…”
Section: Grinding Process Using Ball Millmentioning
confidence: 99%
“…Petrakis et. al., [8] used the population balance approach to examine the effect of the number of balls on particle size reduction in the ball mill during a selective grinding process on low-grade laterite. Based on the research that has been done, there hasn't been much discussion about optimization with the RSM (response surface method) in the grinding process of laterite ore using a ball mill.…”
Section: Introductionmentioning
confidence: 99%